Islamic input in medical program: a realization of a holistic medical education - Osman, Ariff (Zes Rokman Resources, 2016)
An important learning outcome of a medical curriculum is to produce safe doctors over a period of training. The learning process should equip undergraduates to become competent practitioners who are able to provide holistic care to patients, physically, emotionally, psychologically and spiritually. They should have the expertise to attend to patient’s medical and health needs that are delivered in the most ethical manner through mastery of good communication skill and portrayal of compassion during the provision of care. This constitutes the basic attributes of medical professionalism that one should develop during medical training and enhanced throughout one’s career life. For Muslim medical professionals, they need to conform to the Islamic core values that constantly promote the ideals of professionalism, which include positive attitudes such as dedication, respect, compassion, empathy, honesty, altruism, responsibility, integrity, self-improvement, magnanimity and accountability. In achieving this, a holistic medical curriculum should be adopted that ensures applications of behavioural and ethical standards, based on the Islamic worldview, over a period of training. The training process would enable them to execute their duties as safe doctors, at the end of training, with greater accountability and within the realms of acceptable legal rulings for the benefit of the society and also be in conformity with the demands of the Maqasid al Shariáh. This paper discusses the ideals of holistic medical education and the experience of IIUM in implementing its curriculum (Islamic Input in Medical Program, IIMP), which primarily aimed at developing four main attributes of medical professionalism of expertise, ethic, communication and other skills such as leadership, competency in medical fiqh and ethical reasoning skills in approaching medical ethical dilemmas. The challenges, the success and way forward for improvement are also discussed.